2015
DOI: 10.1186/s13071-015-0997-9
|View full text |Cite
|
Sign up to set email alerts
|

Schistosoma mansoni among pre-school children in Musozi village, Ukerewe Island, North-Western-Tanzania: prevalence and associated risk factors

Abstract: BackgroundRecent evidence indicates that pre-school children (PSC) living in S. mansoni highly endemic areas are at similar risk of schistosomiasis infection and morbidity as their school aged siblings. Recognizing this fact, the World Health Organization (WHO) is considering including this age group in highly endemic areas in control programmes using mass drug administration (MDA). However, detailed epidemiological information on S. mansoni infection among PSC is lacking for many endemic areas, specifically i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
36
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(48 citation statements)
references
References 45 publications
10
36
2
Order By: Relevance
“…Schistosomiasis control programs have been undertaken in Rweru area since 2010 (Rwanda Ministry of Health, 2010). The low prevalence of S. mansoni infection observed in the Rweru area, Rwanda among the PSAC in the current study differs from the results of similar studies conducted elsewhere, within the sub-Saharan region, and where prevalence with the Kato-Katz procedure was in the range 7-44% and with the CCA test, was 40-80% (Coulibaly et al, 2013;Odogwu et al, 2006;Ruganuza et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Schistosomiasis control programs have been undertaken in Rweru area since 2010 (Rwanda Ministry of Health, 2010). The low prevalence of S. mansoni infection observed in the Rweru area, Rwanda among the PSAC in the current study differs from the results of similar studies conducted elsewhere, within the sub-Saharan region, and where prevalence with the Kato-Katz procedure was in the range 7-44% and with the CCA test, was 40-80% (Coulibaly et al, 2013;Odogwu et al, 2006;Ruganuza et al, 2015).…”
Section: Discussioncontrasting
confidence: 99%
“…Interestingly, there was a significant association between infection with S. mansoni and going to the lake by the PSAC especially when the children accompany their parents/guardians or older children to the lake. The similar findings have been reported in western Kenya and in Tanzania (Handzel et al, 2003;Ruganuza et al, 2015).…”
Section: Discussionsupporting
confidence: 90%
“…We did not find any association between helminth infections and commonly reported risk factors such as age, hygiene, low socioeconomic status, and history of migration. This is in contrast to other studies, which identified age, poor hygiene, and low socioeconomic status as risk factors for helminth infection in children [ 16 , 17 , 35 , 45 ]. The lack of association with risk factors might be in part due to our sampling strategy, which was primarily powered to detect the prevalence of helminth infection among our study population, rather than association with risk factors.…”
Section: Discussioncontrasting
confidence: 99%
“…mansoni , reporting a high prevalence of up to 50% in well-known high-risk S . mansoni areas around Lake Victoria (North-Western part of Tanzania), where the natural open freshwater serves as a habitat for the intermediate host snails [ 34 , 35 ]. However, a recent systematic review highlighted a low specificity of the POC-CCA test assay in detecting S .…”
Section: Discussionmentioning
confidence: 99%
“…Pre‐treatment infection intensity determines the quantity of schistosome parasites’ antigens that participants are exposed to following PZQ treatment. On the other hand, in endemic areas, participant age correlates with the cumulative history of exposure to schistosome parasites . A study in baboons reported that attenuated schistosome parasite vaccines were effective regardless of the different schistosome infection history (naïve or infected then PZQ‐treated) .…”
Section: Discussionmentioning
confidence: 99%